The Relationship Between Professional Quality of Life and Work Environment Among Nurses in Intensive Care Units - Ahmad Ayed PhD; Moath Abu Ejheisheh PhD; Ibrahim Aqtam PhD; Ahmad Batran PhD; Mosaab Farajallah MSN (SAGE Publishing, 2024)
Nurses in intensive care units (ICUs) face high levels of stress and emotional challenges, making it essential to understand the factors that influence their professional quality of life (ProQoL). This study aimed to investigate the relationship between work environment factors and ProQoL, particularly focusing on burnout, compassion satisfaction, and secondary traumatic stress, among ICU nurses. The Professional Quality of Life (ProQoL) Scale was used to measure these aspects, with an emphasis on the importance of a supportive work environment for enhancing staff well-being and organizational performance. This cross-sectional study was conducted between March and August 2024, involving 162 ICU nurses from hospitals in the southern West Bank. A stratified random sampling method was employed to ensure representativeness. Data collection involved surveys covering socio-demographic information, the Practice Environment Scale-Nursing Work Index (PES-NWI), and the ProQoL scale. Statistical analyses, including descriptive statistics and Pearson correlation, were performed using SPSS. The participants were predominantly young, with 61.7% less than 30 years old, and 65.4% were male. Most held a bachelor's degree (54.9%). The survey indicated that the majority reported average levels of compassion satisfaction (90.7%), burnout (91.4%), and secondary traumatic stress (85.2%). The analysis showed that a moderately positive practice environment was significantly associated with lower levels of burnout and higher levels of compassion satisfaction. Additionally, there was a significant difference in mean Compassion Satisfaction scores according to sleep hours ( F  = 5.475, P  < .05). Nurses who slept more than 8 h had significantly higher Compassion Satisfaction compared to those who slept less than 8 h or exactly 8 h ( P  < .05). ICU nurses generally perceived their work environment positively, though there are opportunities to improve their professional quality of life, particularly by addressing burnout. The findings highlight the need for targeted interventions and further research to enhance job satisfaction and well-being among ICU nurses.